Kritiken av SAOB - Lundbladh, Carl-Erik (LexicoNordica, 2003)
The great historical dictionary of the Swedish language, Dictionary of the Swedish Academy (SAOB), has been published since 1893 onwards. It has not been the object of very many critical reviews. During the first years of publication SAOB was superficially described in praising articles. In the early years of the 20th century some more seriously critical articles were published, the heaviest one though restricted to lamenting omissions and accusing the editors of neglecting the language of modern authors and ordinary people. In recent decades SAOB has been the object of description in informal reviews, which have been only incidentally critical. The dictionary has not been offered substantial and helpful criticism since 1913, perhaps with the exception of a couple of articles reviewing the effects of reforming the editorial work in the twenties. All reviews show a complete lack of concern for semantic principles of the definitions. Also lemmatization as well as user-convenience is rarely or hardly ever an issue. A comprehensive and creative criticism has never been offered. The scale of the work may have daunted reviewers. The fact that the dictionary is not yet completed may be a reason for critics to wait. The fierce defence provided by SAOB when attacked is probably a third reason why there has never been an effecti ve dialogue between the dictionary and its critics.